Cholesterol deprivation affects the fluorescence properties of a ceramide analog at the Golgi apparatus of living cells. - Martin, O C (1993)
Previous studies have established that a fluorescent analog of ceramide, N-[7-(4-nitrobenzo-2-oxa-1,3-diazole)] -6-aminohexanoyl-D-erythro-sphingosine (C6-NBD-Cer), is a vital stain for the Golgi apparatus and a useful tool for studying the sorting and transport of sphingolipids along the secretory pathway in animal cells. Here, we examine the effects of various culture conditions on labeling of the Golgi apparatus of human skin fibroblasts by C6-NBD-Cer and demonstrate that cholesterol deprivation affects the fluorescence properties of the probe at this organelle. Labeling of the Golgi apparatus by C6-NBD-Cer was dramatically reduced in cells grown in medium containing lipoprotein-deficient serum compared to cells grown in medium containing normal serum. Quantitative fluorescence microscopy showed that this apparent reduction in labeling resulted from accelerated photo-bleaching of the fluorescent analog. C6-NBD-Cer labeling of the Golgi apparatus was restored in cholesterol-deprived cells by stimulating endogenous cholesterol biosynthesis with mevalonic acid or by adding exogenous nonlipoprotein cholesterol or low density lipoprotein to the culture medium. In addition, when cells grown in medium containing normal serum were perforated and treated with cholesterol oxidase, an apparent reduction in labeling resulted, further implicating an intracellular pool of cholesterol in the potentiation of C6-NBD-Cer fluorescence. These results demonstrate that cytological studies using C6-NBD-Cer are affected by cholesterol deprivation and suggest that this fluorescent lipid may be used to monitor cholesterol at the Golgi apparatus of living cells.